Prevalence of pulmonary tuberculosis in retroviral positive chest symptomatics in a tertiary care hospital, South India - Sankari, S. Anantha; Sridhar, R. (International Journal of Research in Medical Sciences, 2016)
Background: Human immunodeficiency virus (HIV) associated tuberculosis (TB) remains a major global public health challenge. As this co-infection results in high mortality among retroviral positive patients, we undertook this study to find its prevalence in our region. Methods: Sputum smears from all retroviral positive patients who attended the ART clinic from April 2015 to February 2016 were examined for the presence of Mycobacterium tuberculosis bacilli by fluorescent staining technique. CD4 lymphocyte counting was also done by using BD FACS count instrument. Results: 65 patients were retroviral positive among the 180 patients who came to ART clinic. Of them 43 (66%) were males and 22 (34%) were females. 30 (46%) of retroviral positive patients were sputum positive indicating HIV-TB co-infection. 60% of co-infected patients belong to productive age group of 16-45 years. 93.4% of the co-infected patients had CD4 counts below 350 cells/µl. sputum negative retroviral positive patients had more than 250 CD4 cells/ µl. Conclusions: Our study highlights the fact that HIV-TB co-infection is more prevalent in productive age group and has a positive correlation with lower CD4 counts.